The big bang theory. The complete fifth season [videorecording (DVD)] - Galecki, Johnny; Parsons, Jim, 1973-; Cuoco, Kaley; Helberg, Simon; Nayyar, Kunal; Bialik, Mayim; Rauch, Melissa, 1980- (Warner Home Video, 2012)
Regarding the opposite sex, they're on a steep learning curve. In every other sense, they're geniuses. Join physicists Leonard Hofstadter (Johnny Galecki) and Sheldon Cooper (Jim Parsons) as they ponder black holes, chemical deviations, girls, and other mysteries of the universe.